2022
DOI: 10.1007/s00167-022-07022-2
|View full text |Cite
|
Sign up to set email alerts
|

The anterior hip capsule is thinner in dysplastic hips: a study comparing different young adult hip patients

Abstract: Purpose To investigate the thickness and intra-substance change of anterior capsule of the hip joint, and compare the difference of the capsular features in patients with diferent statuses of hip stability. Methods A retrospective study was performed to review a hip preservation database. Using the lateral center edge angle(LCEA), patients with borderline dysplasia of the hip (BDH) of 20° ≤ LCEA ≤ 25°, femoracetabular impingement(FAI) with LCEA > 30° and dysplasia of the hip (DH) of LCEA < 20° were enrolled an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…Males had a significantly thicker capsule than females, this result is in line with previous studies [1, 7, 10, 20]. Interestingly, the LCEA angle and BTS were not significantly corrected with ACT in our study.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Males had a significantly thicker capsule than females, this result is in line with previous studies [1, 7, 10, 20]. Interestingly, the LCEA angle and BTS were not significantly corrected with ACT in our study.…”
Section: Discussionsupporting
confidence: 93%
“…Bai et al reported that patients with hip dysplasia had a significantly reduced ACT compared with FAIS and borderline DDH patients (4.7 ± 0.6 mm and 4.5 ± 0.8 mm, respectively). They attribute this to the sequence of hip instability, the thinner capsular thickness could be the result of repetitive strains from hip instability [1]. The current study did not include dysplasia or borderline dysplasia patients to exclude the effect of LCEA angle on capsular thickness.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…This measurement strategy allows for a more consistent quantification of the hip capsule than has been shown in previous work. 16 , 17 Repeatable measurement protocols of hip capsule thickness are increasingly important as the focus on the hip capsule continues to rise. Our findings demonstrate an opportunity for future standardization of hip capsule measurements on advanced imaging studies.…”
Section: Discussionmentioning
confidence: 99%